SEROMA IN THE CONTEXT OF BREAST CANCER AND THE INSERTION OF THE NURSE: INTEGRATIVE LITERATURE REVIEW (REMUNOM, 2025)
Seroma is one of the most frequent postoperative complications in the nursing care context for patients undergoing breast cancer treatment. This study aimed to identify, in the scientific literature, evidence regarding the involvement of nurses in caring for women with seroma treated for breast cancer. An integrative review was conducted by searching the PubMed, Cinahl, Scopus, Embase, and LILACS databases. Ten articles were selected according to the eligibility criteria, and the review was reported following the PRISMA guidelines. Most of the studies (70.0%) were published in Europe, 20.0% in South America, and 10.0% in North America, with a notable prevalence of prospective observational studies. The nurse’s role was synthesized into two categories: Postoperative follow-up: Nurses play a crucial role in monitoring and the early detection of complications, such as seroma accumulation, as well as in providing psychosocial support. This follow-up can take place in outpatient settings, through teleconsultations, home visits, or telephone contact, with nurses offering guidance on drain management, pain control, arm exercises, and the use of prostheses. Interventions for seroma management: Nursing actions include dressing changes and, most importantly, percutaneous aspiration after identifying fluctuant areas. The establishment of nurse-led services for seroma aspiration has been reported in several countries, along with the creation of protocols and training programs. In summary, the integration of nurses into the care of breast cancer patients with seroma involves both postoperative follow-up—aimed at early detection of complications—and direct interventions for seroma control, such as dressing procedures and percutaneous aspiration.